"That's the Lowest Place on Earth!" Experiences of the Carceral Spaces of Australian Police Custody for Marginalized Young Men. (May 2020) - Walker, Shelley; Higgs, Peter; Stoové, Mark; Wilson, Mandy
Young men are overrepresented among people detained in police custody in Victoria, Australia, a closed institution that has mostly escaped public scrutiny. Our study sheds light on this underexamined place from the perspective of 28 marginalized young men (aged 19–24) detained there prior to adult prison. Drawing on Bacchi's "What's the problem represented to be?" approach and the subdiscipline of carceral geography, we disrupt the assumed purpose of police custody as a place to simply detain people while awaiting court and/or transfer to prison. We illustrate how police custody, although ostensibly for ensuring the safety and protection of the community, privileges that of some over others, with detrimental effects for marginalized groups. We highlight how harsh, degrading, hostile environments intersected with lived experiences and exacerbated psychological, social, and physical health harms; made possible young men's constitution as dirty, violent, and subhuman; and worked to legitimize breaches of human rights.